KURIKULUM 2013: TINJAUAN TERHADAP PRINSIP DASAR HINGGA PROBLEM IMPLEMENTASI DALAM MATA PELAJARAN PAI - Estu Kinanti; Khairun Nisa (AT-TA'DIB: JURNAL ILMIAH PRODI PENDIDIKAN AGAMA ISLAM, 2022)
The world of education will never be separated from the existence of a curriculum that acts as a guide in the implementation of learning. The curriculum changes according to the demands and developments of the times. Currently, education in Indonesia has applied the 2013 Curriculum as a substitute for the KTSP in the hope of improving the quality of education. The main purpose to be achieved in implementing the 2013 Curriculum is to create a conducive and active learning atmosphere. Students are supposed to be actively involved in the learning process. This can form a better mindset, not only capable in theory but also able to compete in the international world. This curriculum has several basic principles that serve as a reference for implementation at the education level. However, the fact is that the implementation of this curriculum is not always as good as what is stated in the plan but has many shortcomings, both for the educators and the students. The purpose of this research is to explore the 2013 Curriculum from the basic principles, its application, and the problems to be solved in the Islamic Education.